Improvements in Neighborhood Socioeconomic Conditions May Improve Resident Diet. Issue 5 (13th October 2020) - Richardson, Andrea S; Collins, Rebecca L; Ghosh-Dastidar, Bonnie; Ye, Feifei; Hunter, Gerald P; Baird, Matthew D; Schwartz, Heather; Sloan, Jennifer C; Nugroho, Alvin; Beckman, Robin; Troxel, Wendy M; Gary-Webb, Tiffany L; et al.
Abstract: Neighborhood socioeconomic conditions (NSECs) are associated with resident diet, but most research has been cross-sectional. We capitalized on a natural experiment in Pittsburgh, Pennsylvania, in which 1 neighborhood experienced substantial investments and a sociodemographically similar neighborhood that did not, to examine pathways from neighborhood investments to changed NSECs and changed dietary behavior. We examined differences between renters and homeowners. Data were from a random sample of households ( n  = 831) in each of these low-income Pittsburgh neighborhoods that were surveyed in 2011 and 2014. Structural equation modeling tested direct and indirect pathways from neighborhood to resident dietary quality, adjusting for individual-level sociodemographics, with multigroup testing by homeowners versus renters. Neighborhood investments were directly associated with improved dietary quality for renters (β = 0.27, 95% confidence interval (CI): 0.05, 0.50) and homeowners (β = 0.51, 95% CI: 0.10, 0.92). Among renters, investments also were associated with dietary quality through a positive association with commercial prices (β = 0.34, 95% CI: 0.15, 0.54) and a negative association with residential prices (β = −0.30, 95% CI: −0.59, −0.004). Among homeowners, we did not observe any indirect pathways from investments to dietary quality through tested mediators. Investing in neighborhoods may support resident diet through improvements in neighborhood commercial environments for renters, but mechanisms appear to differ for homeowners.